Impact of Digital Payment Factors on Users of the GoPay Digital Payment Platform - Teguh Prakoso; Rina Apriliani; Arif Budiarto; Merissa Fermica Iskandar; Ngurah Pandji Mertha Agung Durya (HM Journals, 2025)
This research aims to analyze impact of digital payment factors on users of the GoPay digital payment platform. This research is included in the type of quantitative research. The population in the study is users of the GoPay digital payment platform. Because the exact number of users of the GoPay digital payment platform is unknown, a saturated sample is used, so the sample for this study was 100 respondents. Hypothesis testing in this study uses multiple linear regression analysis. The results of the study show that the GoPay digital payment platform is an electronic wallet developed by PT GoTo Gojek Tokopedia Tbk which is used as a payment service while using the Gojek application. PT GoTo Gojek Tokopedia Tbk started its business from a motorbike transportation service which then expanded its business network by offering various services. The GoPay digital payment platform is one form of financial technology innovation. Security has a significant effect on the interest of users of the GoPay digital payment platform. Convenience has a significant effect on the interest of users of the GoPay digital payment platform.